2016
DOI: 10.1080/13854046.2016.1251614
|View full text |Cite
|
Sign up to set email alerts
|

Preschool self regulation predicts later mental health and educational achievement in very preterm and typically developing children

Abstract: Early assessment of regulation in addition to behavioral screening may improve the early identification of preschool children at mental health risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 51 publications
4
82
1
1
Order By: Relevance
“…Seven studies 13,32,33,[35][36][37]40 were entered as both diagnostic instruments (categorical data) and rating scales (continuous data) in the meta-analysis. The Extremely Premature Infants Cure (EPICure) Study was entered in both dimensional and categorical analyses because the same population was assessed at different times and with distinct evaluation methods: by Samara et al 41 40 2017 was also entered in both categorical and dimensional analyses because information from the dimensional scale (SDQ) was collected from the subjects at 2 years of age, and a categorical diagnosis was obtained at 9 years of age with the Development and Wellbeing Assessment (DAWBA). In 1 publication 36 researchers included 2 cohorts, but data were only available under request from the 2004 Pelotas cohort data managers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven studies 13,32,33,[35][36][37]40 were entered as both diagnostic instruments (categorical data) and rating scales (continuous data) in the meta-analysis. The Extremely Premature Infants Cure (EPICure) Study was entered in both dimensional and categorical analyses because the same population was assessed at different times and with distinct evaluation methods: by Samara et al 41 40 2017 was also entered in both categorical and dimensional analyses because information from the dimensional scale (SDQ) was collected from the subjects at 2 years of age, and a categorical diagnosis was obtained at 9 years of age with the Development and Wellbeing Assessment (DAWBA). In 1 publication 36 researchers included 2 cohorts, but data were only available under request from the 2004 Pelotas cohort data managers.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers reported patient assessment during childhood in 8 studies, 13, 32, 34 -38, 40 during adolescence in 3 studies, 30,31,33 and during adulthood in 1 study. 39 Researchers reported female pre dominance in 5 studies, 30,31,35,37,39 male predominance in 4 studies, 13,33,38,40 and did not report on sex in 3 studies. 32,34,36 Twenty-nine studies (3504 individuals) were included for analysis of ADHD symptomatology FRAnz et al according to ADHD rating scales.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The few longitudinal studies that have investigated the prevalence of behavioral symptoms or disorders in children and adolescents who were born preterm or low birth weight have shown that the increased prevalence of problems persists over time and may have greater stability in individuals born preterm compared with those born at term or with normal birthweight [2,[12][13][14][15][16]. Many of these previous studies employed cross-sectional analysis techniques which are not able to detect variation in individual trajectories; or they focussed on specific disorders such as ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Supports in these domains may be required for some students to make the age appropriate academic skill gains of which they are capable (Ysseldyke et al, 2017). There are many examples of literature and methods available to aid school personnel in supporting student executive functioning (Dawson and Guare, 2003), self-regulation (Shanker, 2012;Woodward et al, 2017), and social skills (Reid et al, 2007;Frankel and Whitham, 2011). However, these domains are harder to define and less amenable to direct measurement (i.e., as opposed to IQ scores), as Foster-Cohen and Mirfin-Veitch (2017) noted that:…”
Section: Verbal Communication Visual Cognitive and Literacymentioning
confidence: 99%